Shortage of Domestic Savings and Investments as a Barrier to Economic Development - Filipović, Milorad; Nikolić, Miroljub; Katić, Goran (Industrija, 2015)
In this paper we have analyzed the main macroeconomic parameters and provided projections of their movements in the Republic of Serbia for the period 2015-2017. Projections of the main macroeconomic aggregates are based on the use of a tailored financial programming model (MEP1) that represents a set of statistical and econometric methods with a view to correlating the endogenous and exogenous variables of the entire macroeconomic system. The task of the applied financial programming model was to describe two scenarios of economic development of Republic of Serbia until 2017. As the main conclusion of this paper, the stance that there is no long-term and sustainable development of Serbia without a significantly higher share of domestic savings in the distribution of GDP as well as changes in its structure in terms of strengthening dinar savings can be stated. Main contribution of the Paper should be argumentation that development model of Serbia from the first decade of XXI Century, based on substantially increased aggregate demand financed from privatization revenues and rising indebtedness of country has to be changed in favor of higher domestic savings, investments and on that ground improved competitiveness of national economy.
Keywords: Model; Financial programming; Savings; Investments; Development